EVALUASI REFLEKTIF PENDIDIKAN KARAKTER DAN AGAMA BUDDHA DI LINGKUNGAN KELUARGA - Hesti Sadtyadi (Widyacarya: Jurnal Pendidikan, Agama dan Budaya, 2019)
Education Buddhism does not stand alone. Religious education is an integral part inbuilding the character of the child. Religious education will be embedded in the values of morality,intellectuality, besides nationalism to the nation and state life to Buddhism. Given the charactereducation experienced the longest process in the family, and religious values should be embeddedfrom the family environment and child behavior problems encountered in the field, then theformulation of the issues raised is how the process of character education and religion can worktogether through education in the family? This research is combined , using descriptive qualitativeapproach . As a result of the study are seven ways to be done to foster the main virtues ( goodcharacter ) , that empathy , conscience , self-control , respect , kindness , tolerance , and justice. The seventh kind of virtue is what can make the man of quality . The technique can be used toperform character education and religion in a family environment is by blending educationBuddhism , character education within the family , by instilling the values of the precepts andmorality , in the form of real-life examples behavioral will be able to form a good character , inaccordance with a family destination . Parents should be examples of good models .